Time Reallocation of Physical Behaviours Induced by Endurance Exercise in Physically Active Individuals - Suarez-Reyes, M (Taylor and Francis Ltd., 2023)
Increasing moderate-vigorous physical activity (MVPA) through exercise requires reallocating time from other physical behaviour(s). We aimed to determine the reallocations induced by endurance exercise in physically active individuals. We also searched for behavioural compensatory responses, and explored the effect of exercise on daily energy expenditure. Fourteen participants (8 women; median age 37.8 [IQR 29.9–48.5] yr) exercised on Monday, Wednesday, and Friday mornings (cycling MVPA, 65 min/session; “exercise days”), and avoided exercising on Tuesday and Thursday (“rest days”). Time spent on sleep, sedentary behaviour, light-intensity physical activity, and MVPA was determined each day by accelerometers and logs. An energy expenditure index was computed considering minutes spent on each behaviour and fixed metabolic equivalents. We found that all participants had lower sleep and higher total (including exercise) MVPA on exercise days compared to rest days. Thus, on exercise vs. rest days, sleep was lower (490 [453–553] vs. 553 [497–599] min/day, respectively, P < 0.001), and total MVPA was higher (86 [80–101] vs. 23 [15–45] min/day, respectively; P < 0.001). No differences in other physical behaviours were detected. Notably, exercise not only induced reallocations (i.e. less time in other behaviours) but also behavioural compensatory responses in some participants (e.g. increased sedentary behaviour). This rearrangement of physical behaviours manifested in exercise-induced increases in energy expenditure from 96 to 232 MET × min/day. In conclusion, active individuals reallocated time from sleep to accommodate morning exercise. Yet exercise induced variable rearrangements of behaviours, with some individuals manifesting compensatory responses. Understanding individual rearrangements may help improve exercise interventions. © 2023 European College of Sport Science.